PERAN ORANG TUA DALAM MENERAPKAN PERILAKU SOPAN - Lusianty, Mery; R, Marmawi; Miranda, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aim of this research was to describe the role of parents in apply manners of aged 5-6 years. The method use isn this research is descriptive method with a qualitative research approach. Data subjects in this research are 2 parents or 2 families who have children aged 5-6 years at Mekar Sari Village, Ketapang Regency. The techniques used in this research were observation, interview, and documentation using data collection tools like is observation guidelines, interview guides, and documentation picture. The results of data analysis show that the role of parents in apply manners of aged 5-6 years at Mekar Sari Village, Ketapang Regency conductued by parents through exemplary the involvements of reinforcement and togetherness is implementes poorly, because parents don?t have provide direct exempels and involvement in applying manners to their children, parents also have nor provided reinforcement to their children and don?t have time together with family, because parents are busy at work.Keyword : Apply Manners, Reinforcement, The Role Of Parents.